The neglected approach to poverty alleviation - Tahir, Ibrahim Nuhu (Kulliyyah of Economics, International Islamic University Malaysia, 2019)
According to different studies the world is suffering from chronic poverty, with around 3 billion of its population living below $2.50 per day and 80% living below $10 (Shah, 2014). The effects of poverty indiscriminately cut across race, nationality and religion. Governments, non-governmental organizations and international bodies have tried numerous methods to at least remove hardcore and extreme poverty if not eradicate poverty completely. Unfortunately, regardless of the immense financial and human resources dedicated to this effort it has failed except for a few instances. The key cause of this failure is the dichotomy created between Sharīʿah and worldly knowledge. This has led to abandonment of the methodology used by the early generations such as the era of ʿUmar ibn ʿAbd Al-ʿAzīz (raḥimahullāh), who fully depended on the Qurʾān and Sunnah in his administration to tackle the issue. In Islam poverty is described as a disease affecting the heart hence requiring a spiritual cure. Therefore, Islam recognizes spiritual and physical poverty. This is contrary to the popular secular view that poverty is merely a material deficiency. This is evidence of the disparity between Islam’s position on poverty as a trial and the secular view that it is a situation to be resolved only physically. This paper addresses poverty alleviation through the Islāmic Spiritual Approach and the Islāmic Material Approach which are based on crystal clear divinely guided injunctions from Qurʾān and Sunnah.